Unusual Deaths of Silesian Piasts in the 15th Century – Selected Cases - Kanas, Rafał; Grancow, Patryk; Gorzkiewicz, Bartłomiej; Chyliński, Piotr; Kołata, Zuzanna; Jastrząbek, Jakub; Agnieszka Gralak (Vade Nobiscum, tom XXV/2025: Varia, 2025)
In the 15th century, the Silesian Piasts no longer had the same political significance as their 14th-century predecessors; there were no more figures like Bolko II the Small or Władysław Opolczyk. At the same time, the Piasts continued to rule over parts of Silesia, being subordinate to the Czech kings. They were mentioned episodically by Jan Długosz in his Annals on the occasion of more important events. Długosz devoted several times more space to the unusual deaths of the Piasts, such as: Przemysław II of Cieszyn, who was killed on the road, Jan of Ziębice, who fell in battle with the heretics, Baltazar Żagański, who died in a dungeon, and Rudolf Żagański, a mercenary who fought for the Teutonic Order. This text describes the circumstances of the deaths mentioned, and verifies the reliability of Jan Długoszʼs message with other available sources and research by contemporary historians.